Hearing aid effectiveness after aural rehabilitation - individual versus group (HEARING) trial: RCT design and baseline characteristics - Heagerty Patrick J; Liu Chuan-Fen; Souza Pamela E; Collins Margaret P; Amtmann Dagmar; Yueh Bevan (BMC, 2009)
Abstract Background Hearing impairment is the most common body system disability in veterans. In 2008, nearly 520,000 veterans had a disability for hearing loss through the Department of Veterans Affairs (VA). Changes in eligibility for hearing aid services, along with the aging population, contributed to a greater than 300% increase in the number of hearing aids dispensed from 1996 to 2006. In 2006, the VA committed to having no wait times for patient visits while providing quality clinically-appropriate care. One approach to achieving this goal is the use of group visits as an alternative to individual visits. We sought to determine: 1) if group hearing aid fitting and follow-up visits were at least as effective as individual visits, and 2) whether group visits lead to cost savings through the six month period after the hearing aid fitting. We describe the rationale, design, and characteristics of the baseline cohort of the first randomized clinical trial to study the impact of group versus individual hearing aid fitting and follow-up visits. Methods Participants were recruited from the VA Puget Sound Health Care System Audiology Clinic. Eligible patients had no previous hearing aid use and monaural or binaural air-conduction hearing aids were ordered at the evaluation visit. Participants were randomized to receive the hearing aid fitting and the hearing aid follow-up in an individual or group visit. The primary outcomes were hearing-related function, measured with the first module of the Effectiveness of Aural Rehabilitation (Inner EAR), and hearing aid adherence. We tracked the total cost of planned and unplanned audiology visits over the 6-month interval after the hearing aid fitting. Discussion A cohort of 659 participants was randomized to receive group or individual hearing aid fitting and follow-up visits. Baseline demographic and self-reported health status and hearing-related measures were evenly distributed across the treatment arms. Outcomes after the 6-month follow-up period are needed to determine if group visits were as least as good as those for individual visits and will be reported in subsequent publication. Trial Registration NCT00260663